Possibilities in Recycling Magnetic Materials in Applications of Polymer-Bonded Magnets - Rösel, Uta; Drummer, Dietmar (Magnetism, 2022)
Polymer-bonded magnets have increased significantly in the application of drive technology, especially in terms of new concepts for the magnetic excitation of synchronous or direct current (DC) machines. To satisfy the increasing demand of hard magnetic filler particles and especially rare earth materials in polymer-bonded magnets, different strategies are possible. In addition to the reduction in products or the substitution of filler materials, the recycling of polymer-bonded magnets is possible. Different strategies have to be distinguished in terms of the target functions such as the recovery of the matrix material, the filler or both materials. In terms of polymer-bonded magnets, the filler material—especially regarding rare earth materials—is important for the recycling strategy due to the limited resource and high costs. This paper illustrates two different recycling strategies relative to the matrix system of polymer-bonded magnets. For thermoset-based magnets, a thermal strategy is portrayed which leads to similar magnetic properties in terms of the appropriated atmosphere and process management. The mechanical reusage of shreds is analyzed for thermoplastic-based magnets. The magnetic properties are reduced by about 20% and there is a change in the flow conditions and with that, an influence on the pole accuracy<br